The Impact of Think Pair Share and Two Stay Two Stray Learning Model Towards Learning Outcomes and Cooperation Ability - Hidayat, Teriana Mardha; Muhson, Ali (Dinamika Pendidikan, 2018)
This research aimed to find out the effectiveness of Think Pair Share (TPS) and Two Stay Two Stray (TSTS) methods in improving student learning outcomes and cooperation skills. The population in this research were all students of class X IPS SMA N 2 Banguntapan in the academic year 2016/2017 which consisted of 98 people, divided into four parallel classes. The sampling technique is cluster sampling to classify the students into three classes, divided in experiment class 1, experiment 2, and control class which determined randomly. The data collection methods used were documentation, test, and observation techniques. The research type is quasi experiment with pretest-posttest control group design. The analysis technique used was descriptive statistical analysis and Multivariate Analysis of Variances (MANOVA). The results showed that TPS and TSTS methods were proven to be more effective than conventional ones in improving students’ learning outcomes. Students who were taught by TPS and TSTS methods were also proven to have better collaborative skills than students taught by conventional methods.